What do private providers of home care want? An analytical framework - Julien Mercille; Luciana Lolich (Critical Public Health)
Private for-profit home care providers are key participants in European long-term care regimes. Yet, their policy preferences toward market making and market development remain under-researched. We present an analytical framework that identifies and explains those preferences. It outlines three key types of policies that shape home care markets: regulatory, financial and labour policies. We illustrate private providers’ views on those policies by reference to Ireland’s home care regime. Irish home care is a compelling case for this study. A major package of regulatory reforms is currently being introduced and private providers have outlined clear preferences about it. Our paper is based on interviews with 14 leading individuals involved in the home care sector. We find and explain how private providers wish to increase regulation over their activities; to split purchaser and provider roles; to reduce private forms of financing; and to expand the pool of labour available to them. We discuss how those preferences shed light on the political economic power dynamics that shape the Irish care regime. Our analytical framework may be applicable to other welfare markets at different stages of development and in other institutional contexts.